2018
DOI: 10.1002/anie.201804592
|View full text |Cite
|
Sign up to set email alerts
|

The Broad Aryl Acid Specificity of the Amide Bond Synthetase McbA Suggests Potential for the Biocatalytic Synthesis of Amides

Abstract: Amide bond formation is one of the most important reactions in pharmaceutical synthetic chemistry. The development of sustainable methods for amide bond formation, including those that are catalyzed by enzymes, is therefore of significant interest. The ATP‐dependent amide bond synthetase (ABS) enzyme McbA, from Marinactinospora thermotolerans, catalyzes the formation of amides as part of the biosynthetic pathway towards the marinacarboline secondary metabolites. The reaction proceeds via an adenylate intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 27 publications
0
42
0
2
Order By: Relevance
“…At the moment however, such methods lack broad scope (as might be expected of enzymatic methods), often not tolerating even secondary amines [32,33] and require activated AMP-esters which hydrolyze under the reaction conditions [34] and can require large excesses to achieve desirable yields. While recent reports have sought to address both issues, [35][36][37] such technologies can be presently of interest as complements to SPPS in the form of alternative strategies to native chemical ligation or cyclization. [38][39][40] Another alternative approach to strictly catalytic methods is the recycling of reagents and solvents.…”
Section: Alternative Approaches To Noncanonical Amidationmentioning
confidence: 99%
“…At the moment however, such methods lack broad scope (as might be expected of enzymatic methods), often not tolerating even secondary amines [32,33] and require activated AMP-esters which hydrolyze under the reaction conditions [34] and can require large excesses to achieve desirable yields. While recent reports have sought to address both issues, [35][36][37] such technologies can be presently of interest as complements to SPPS in the form of alternative strategies to native chemical ligation or cyclization. [38][39][40] Another alternative approach to strictly catalytic methods is the recycling of reagents and solvents.…”
Section: Alternative Approaches To Noncanonical Amidationmentioning
confidence: 99%
“…While the canonical biosynthesis carried out by NRPSs has been well-studied, an increasing number of examples exist in which NRPS domains are shown to catalyze unusual activities 4 . These activities include amide formation by adenylation domains 5,6 , condensation domain-catalyzed amide formation between a propionate and a pteridine ring in an unusual “pepteridine” natural product 7 , thioesterase domain-mediated condensation of two α-keto carboxylates in the production of quinone or furanone derivatives 8,9 , β-lactone and β-lactam cyclization by thioesterase domains 1012 , and a Dieckmann condensation catalyzed by an unusual reductase domain, which lacks the conventional catalytic triad, involved in the release of cyclopiazonate tetramic acid neurotoxin 13 . Some of these activities reflect more limited changes in the overall synthetic program, for example, the use of an alternate nucleophile to attack the adenylate directly in formation of the amide bond that bypasses the PCP-bound thioester intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was shown that the rate of hydroxamate formation correlates with other nonenzymatic quenching reactions, when l ‐Pro is employed as a nucleophile instead of hydroxylamine, for instance . Nonenzymatic quenching of adenylates with various amine nucleophiles could have synthetic applications . The main problem with Fe 3+ ‐based detection of hydroxamates is poor sensitivity in the high micromolar range and instability of the complex.…”
Section: Kinetic Profilingmentioning
confidence: 99%